PENGARUH OLAHRAGA KOMPETITIF TERHADAP MOTIF BERPRESTASI - Ma’ruful Kahri (Lambung Mangkurat University, 2013)
This research based on the thought that for facing high competitve era in the future it needed human resources who have strong chacteristic that will be able to survive in their live and have high achievement orientation. According to scholars that motivation for achievement can be taught to the group or organization through ‘achievement training’ in relation to reach great attains. The aim of this research is to find out on how high performances in the student ahletes can be able to create high achievement oriented-characteristics. Method of research used is ex post de facto, and motivation for achievement is used for data collection. The instrumen of motivation for achievement has been structured and developed by researcher based on five stages following Likert Model. From result of this study is recommended that athletics of kompetitif exercising every day without differentiating athletic branch earn internalization motivate to have achievement. Keyword : Achievement Motivation; Sport Competitive; PPLM